1991
DOI: 10.3109/00952999108992817
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Amantadine and Desipramine Combined with Psychotherapy for Treatment of Cocaine Dependence

Abstract: We conducted a single-blind, random assignment, placebo-controlled, 12-week comparison of desipramine hydrochloride and amantadine hydrochloride as adjunctive treatments to counseling for cocaine dependence. Subjects were 54 outpatients who met DSM III-R criteria for active cocaine dependence and who completed a minimum of 2 weeks of treatment. Subjects treated with fixed doses of 200 mg/day desipramine (N = 17), 400 mg/day amantadine-placebo (N = 16), and placebo (N = 21) did not differ for lifetime cocaine u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(43 citation statements)
references
References 29 publications
2
41
0
Order By: Relevance
“…For example, cocaine withdrawal in humans in the outpatient setting is characterized by severe depressive symptoms combined with irritability, anxiety, and anhedonia lasting several hours to several days (i.e., the "crash") and may be one of the motivating factors in the maintenance of the cocaine-dependence cycle (Gawin and Kleber, 1986). Inpatient studies have shown similar changes in mood and anxiety states, but they generally are much less severe (Weddington et al, 1991 ). Opiate withdrawal is characterized by severe dysphoria, and ethanol withdrawal produces dysphoria and anxiety.…”
Section: Neural Substrates For the Negative Reinforcement Associated mentioning
confidence: 82%
“…For example, cocaine withdrawal in humans in the outpatient setting is characterized by severe depressive symptoms combined with irritability, anxiety, and anhedonia lasting several hours to several days (i.e., the "crash") and may be one of the motivating factors in the maintenance of the cocaine-dependence cycle (Gawin and Kleber, 1986). Inpatient studies have shown similar changes in mood and anxiety states, but they generally are much less severe (Weddington et al, 1991 ). Opiate withdrawal is characterized by severe dysphoria, and ethanol withdrawal produces dysphoria and anxiety.…”
Section: Neural Substrates For the Negative Reinforcement Associated mentioning
confidence: 82%
“…For example, cocaine withdrawal in humans in the outpatient setting is characterized by severe depressive symptoms combined with irritability, anxiety, and anhedonia lasting several hours to several days (i.e., the "crash") and may be one of the motivating factors in the maintenance of the cocaine-dependence cycle (Gawin and Kleber 1986). Inpatient studies of cocaine withdrawal in cocaine-dependent subjects have shown similar changes in mood and anxiety states, but they generally are much less severe (Weddington et al 1991). Opiate withdrawal is characterized by severe dysphoria, and alcohol withdrawal produces pronounced dysphoria and anxiety.…”
Section: Motivational Components Of Withdrawalmentioning
confidence: 99%
“…Therapeutic effects of antidepressants in cocainedependent patients have been examined in several trials, with mostly disappointing results. [10][11][12][13][14][15][16][17][18] Nevertheless, compelling reasons exist to consider such agents. Although cocaine is a potent dopamine reuptake blocker, longterm use is associated with down-regulation of dopaminergic systems.…”
Section: Discussionmentioning
confidence: 99%